Fundamental Role of Neurochemicals Aberration in the Pathogenesis of Autism Spectrum Disorders - Meguid, Nagwa A.; Ahmed, Hanaa H.; Gad, Manal A.; Abdel Baki, Olwaya M.; Aziz, Samia S.; Eskander, Emad F. (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this research was to establish the perturbation of reliable biomarkers implicated in the pathophysiology of autism to help in the early diagnosis and to be as targets in the treatment of autism spectrum disorders (ASDs) in children and to spotlight into the complex crosstalk between these biomarkers. PATIENS AND METHODS: This study included 90 autistic children aged from 2 to 7 years old, who were classified into two groups, the atypical autism of 30 children and the childhood autism. The childhood autism group was further divided into mild-moderate autism group and severe autism group each of 30 children. The control group included 30 matched healthy children. All the participants were subjected to full psychiatric examinations, psychological investigations, and biochemical measurements, including gamma-aminobutaric acid (GABA), serotonin, dopamine (DA) in plasma, and brain-derived neurotrophic factor (BDNF) in serum. RESULTS: The autistic groups showed a highly significant increase in GABA, serotonin, DA, and BDNF levels compared to the control. Of note, the levels of GABA, DA, and BDNF were significantly increased with the increased disease severity. Furthermore, a significant positive correlation between BDNF levels and both GABA and DA levels in the childhood autism group has been recorded. CONCLUSION: The present clinical setting provides new insight into the fundamental role of BDNF in the brain of autistic children as any alterations of its level due to GABA increment cause change in serotonin and DA levels which have empirical evidence in the pathophysiology of ASD. The results received in this research, create a fertile base for the setup of particular targets in the intervention of this ailment.